Complex Human-Shark Conflicts Confound Conservation Action - Simpfendorfer, Colin A.; Heupel, Michelle R.; Kendal, Dave (Frontiers in Conservation Science, 2021)
Human-wildlife conflicts are a growing phenomenon globally as human populations expand and wildlife interactions become more commonplace. While these conflicts have been well defined in terrestrial systems, marine forms are less well understood. With concerns grow for the future of many shark species it is becoming clear that a key to conservation success lies in changing human behaviors in relation to sharks. However, human-shark conflicts are multidimensional, each with different ecological, social and economic implications. Sharks have functional roles as occasional predators of humans and competitors with humans for fish stocks. In addition, and unlike most terrestrial predators, sharks are also important prey species for humans, being a source of animal protein and other products taken in fisheries. These functional roles are complex and often inter-dependent which can lead to multiple kinds of conflict. Shark management for conservation and human safety is also leading to conflict between different groups of people with different values and beliefs, demonstrating that human wildlife conflict can be a proxy for human-human conflict in the marine domain. Sharks are iconic species in society, being both feared and revered. As such human beliefs, attitudes and perceptions play key roles that underpin much human-shark conflict and future work to understanding these will contribute significantly to solutions that reduce conflict and hence improve conservation outcomes.